Fleksibilitas Tanpa Batas: Analisis Kualitatif Beban Psikologis Dan Kesejahteraan Subyektif Pekerja Kreatif Digital Di Denpasar - Wahyu Bagas Kinandana; I Putu Dharmawan Pradhana; Ni Ketut Anjani; Putu Purnama Dewi (Journal of Innovative and Creativity, 2026)
The shift from conventional tourism to digital creative economy in Denpasar has created a dynamic yet vulnerable class of digital creative workers facing glorified work flexibility. This study aims to explore the phenomenological experiences of digital creative workers (photographers, videographers, graphic designers) regarding psychological burden and subjective well-being (SWB). Employing a qualitative transcendental phenomenology approach, data were gathered from eight key informants in Denpasar via purposive and snowball sampling, using in-depth interviews, participant observation, and document analysis. Data analysis followed phenomenological reduction, noematic-noetic analysis, and essence synthesis, enhanced by source triangulation. Findings reveal the "autonomy paradox" where time control becomes 24/7 digital imprisonment, driven by subjective revisions, financial precarity, and high-strain conditions per JDCS model. Despite heavy psychological loads from role ambiguity and self-exploitation, workers demonstrate resilience through digital boundary management, emotional healing rituals, and communal support, achieving moderate-to-high SWB. In conclusion, flexibility transforms from burden to manageable asset via adaptive coping, recommending fair contracts and mental health literacy.